WATER TABLE DEPTHS TRENDS IDENTIFICATION FROM CIMATOLOGICAL ANOMALIES OCURRED BETWEEN 2014 AND 2016 IN A CERRADO CONSERVATION AREA IN THE MEDIO PARANAPANEMA HYDROGRAPHIC REGION/SP-BRAZIL - Manzione, Rodrigo Lilla [UNESP] (Univ Federal Goias, Inst Estudos Socio-ambientais, 2018)
Allying temporal and spatial dimensions at phenomena analysis can bring answers that traditional geographical spatial data analysis alone would not revel. However, gathering scales that do not vary in the same way, such as space and time, is not routine in geosciences due to the complex structure of these data. The aim of this study was to investigate the behavior of groundwater resources against the climatic anomalies occurred in the State of Sao Paulo between 2013-2016 in a representative area of the Medio Paranapanema hydrographic region (UGRHI-17), in time and space. A monitoring network of water table depths and an automatic climatological station were installed in the Ecological Station of Santa Barbara, municipality of Aguas de Santa Barbara (SP), Brazil, to collect groundwater and climatological data between September 2014 and August 2016 at 32 wells. Time series modelling showed that the climatic inputs influenced the behavior of the groundwater levels, indicating elevation trends in the studied period. On the other hand, the spatial analysis revealed differentiated patterns of elevation between EEcSB basins, mainly as a land use function. This information is important for groundwater management, water dependable activities planning and studies about the natural resources capacity of specific areas.
Keywords: time series; groundwater; monitoring; PIRFICT model